Double-layer composite diaphragm and preparation method thereof and battery
Through the design of a double-layer composite separator, the combination of sodium silicate and phase change flame retardant materials is used to solve the electrochemical and safety performance problems caused by dendritic lithium dendrites in lithium metal batteries, and the efficient electrochemical performance of the battery is achieved and The combination of safety performance reduces the risk of thermal runaway.
Patent Information
- Application Number
- CN202411337961.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-09-25
AI Technical Summary
Dental lithium dendrites produced by lithium metal during electroplating and peeling lead to a decrease in the electrochemical and safety performance of the battery, and there is a risk of short-circuiting, which may cause thermal runaway and explosion accidents. The existing technology cannot take into account excellent electrochemical performance and Safety performance.
A double-layer composite separator is used. The first membrane layer is composed of sodium silicate and polymer fibers. The second membrane layer is composed of phase-change flame retardant materials and polymer fibers to form a necklace structure. It is prepared by electrospinning and hot pressing to ensure the separator. The high porosity and mechanical strength prevent lithium dendrites from growing and reduce the risk of thermal runaway.
It achieves good electrochemical and safety performance of the battery, reduces the probability of thermal runaway, improves the mechanical strength of the diaphragm and the electrolyte retention rate, delays the peak temperature of thermal runaway, and significantly improves the application safety of lithium metal batteries.
Smart Images

Figure CN118867574B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries and relates to a double-layer composite diaphragm and a preparation method thereof and a battery. Background Art
[0002] Lithium metal has high theoretical specific capacity, low density and low chemical potential. Using it as a negative electrode material can perfectly meet the needs of high energy density and is expected to develop further in new energy vehicles, mobile electronics, wearable electronic products and other fields.
[0003] However, lithium metal will produce uncontrollable branched lithium dendrites (lithium dendrites for short) during the electroplating and stripping process, which will significantly reduce the electrochemical and safety performance of the battery. What is more serious is that the unlimited growth of branched lithium dendrites will have the risk of piercing the diaphragm. Once this happens, the positive electrode will be directly short-circuited, causing the local temperature to rise sharply, thereby triggering thermal runaway and leading to major safety accidents such as combustion or even explosion.
[0004] The existing technology often adjusts the electrolyte composition, changes the lithium ion solvation environment, and promotes the uniform deposition of lithium ions on the negative electrode surface to avoid the formation of lithium dendrites; or changes the kinetics of lithium metal reduction, that is, by controlling the nucleation and growth rate of lithium metal, guides the reduction of metallic lithium in large blocks or flakes. However, the methods disclosed in the prior art cannot take into account excellent electrochemical performance, and the first efficiency and cycle performance of the prepared battery are poor.
[0005] Therefore, providing a strategy that can balance safety performance and electrochemical performance is a technical problem that needs to be solved urgently. Summary of the invention
[0006] In view of the above problems existing in the prior art, the object of the present invention is to provide a double-layer composite diaphragm and a preparation method thereof and a battery.
[0007] To achieve the above object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a double-layer composite diaphragm, comprising a first membrane layer and a second membrane layer stacked together, wherein the first membrane layer comprises a first fiber skeleton, the first fiber skeleton comprises a mixture, the mixture comprises sodium silicate and a first polymer, the second membrane layer comprises a second fiber skeleton, the second fiber skeleton comprises second polymer fibers, and the second polymer fibers are partially wrapped with a phase change flame retardant material to form a necklace structure.
[0009] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0010] Preferably, the thickness of the first film layer is A, the thickness of the second film layer is B, and 1 / 3≤A / (A+B)≤2 / 3.
[0011] Preferably, the phase change flame retardant material includes at least one of Fe3P, (NH4)2·HPO4, (NH4)·H2PO4, aluminum hydroxide, magnesium hydroxide, red phosphorus, ammonium polyphosphate, zinc borate and antimony oxide, preferably Fe3P and / or aluminum oxide.
[0012] Preferably, the first polymer includes at least one of polyvinyl alcohol (PVA), polyvinylidene fluoride (PVDF), polypropylene (PP), polyethylene (PE), polyethylene terephthalate (PET), polymethyl methacrylate (PMMA) and polyethylene oxide (PEO), preferably PVA.
[0013] Preferably, the second polymer fiber comprises at least one of polyvinyl alcohol, polyvinylidene fluoride, polypropylene, polyethylene, polyethylene terephthalate, polymethyl methacrylate and polyethylene oxide, preferably PVA.
[0014] In one embodiment, the melting temperature of the first polymer is t1, the melting temperature of the second polymer is t2, the melting temperature of the phase change flame retardant material is t3, and the melting temperature of the sodium silicate is t4, t1< t3< t4, t2< t3< t4. In this case, when the melting temperature of the first polymer and / or the second polymer is exceeded, the first polymer and / or the second polymer melts first, and at the same time blocks the ion transmission path. When thermal runaway occurs at a higher temperature, the phase change flame retardant material melts and absorbs heat, reducing the peak temperature of thermal runaway.
[0015] Preferably, the mass proportion of the sodium silicate in the first film layer is 33.3%-50.0%.
[0016] Preferably, the mass proportion of the phase change flame retardant material in the second film layer is 20.0%-50.0%.
[0017] Preferably, the porosity of the double-layer composite diaphragm is 37%-46%.
[0018] In a second aspect, the present invention provides a method for preparing the double-layer composite diaphragm as described in the first aspect, comprising the following steps:
[0019] (1) Providing electrospinning solution:
[0020] adding sodium silicate to the first polymer glue to obtain a first solution;
[0021] Adding a phase change flame retardant material to the second polymer glue to obtain a second solution;
[0022] (2) Electrospinning:
[0023] Electrospinning is performed using the first solution and the second solution respectively to obtain a first spinning membrane and a second spinning membrane;
[0024] (3) Hot pressing treatment:
[0025] The first spinning membrane and the second spinning membrane are stacked together and hot pressed to obtain the double-layer composite membrane, which includes a first membrane layer and a second membrane layer stacked together, wherein the first spinning membrane forms the first membrane layer and the second spinning membrane forms the second membrane layer.
[0026] Preferably, in step (1), the viscosity of the first polymer glue is μ1, 50 cP≤μ1≤20000 cP.
[0027] Preferably, after the sodium silicate is added, heating and stirring are performed to form a first solution in a gel state.
[0028] Preferably, in step (1), the viscosity of the first solution is μ2, 50 cP≤μ2≤30000 cP.
[0029] Preferably, in step (1), the viscosity of the second polymer glue is μ3, 50 cP≤μ3≤20000 cP.
[0030] Preferably, after the phase change flame retardant material is added, heating and stirring are performed to form a second solution in a gel state.
[0031] Preferably, in step (1), the viscosity of the second solution is μ4, 50 cP≤μ4≤30000 cP.
[0032] Preferably, in step (2), the volume V1 of the first solution and the volume V2 of the second solution satisfy: 1 / 3≤V2 / (V2+V1)≤2 / 3.
[0033] Preferably, the temperature of the hot pressing in step (3) is 80°C-220°C.
[0034] Preferably, the hot pressing pressure in step (3) is 10 kPa-30 kPa.
[0035] Preferably, the hot pressing time in step (3) is 0.5h-10h.
[0036] In a third aspect, the present invention provides a battery comprising a positive electrode, a negative electrode, a diaphragm and an electrolyte, wherein the diaphragm is the double-layer composite diaphragm described in the first aspect or the double-layer composite diaphragm prepared by the method described in the second aspect, wherein the first film layer is arranged close to the negative electrode, and the second film layer is arranged close to the positive electrode.
[0037] In the present invention, the first film layer needs to be arranged close to the negative electrode and the second film layer needs to be arranged close to the positive electrode. This is because: the second film layer contains phase change flame retardant materials, and some phase change flame retardant materials are conductive. The phase change flame retardant materials may not be completely wrapped, and it is necessary to use the insulation of the first film layer to separate them; if some phase change flame retardant materials (such as Fe3P) are arranged close to the negative electrode, they will react with lithium ions from the positive electrode at low potential, so the second film layer containing them should be arranged close to the positive electrode.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] (1) The double-layer composite diaphragm of the present invention has good electrochemical performance, good safety performance and excellent effect of reducing the probability of thermal runaway. The area shrinkage of the double-layer composite diaphragm at 200°C is less than or equal to 14.8%; the battery made of the double-layer composite diaphragm is charged and discharged at a current of 1A / g, and its first efficiency is above 86.4%, and the capacity retention rate after 2000 cycles is above 82.4%.
[0040] (2) The present invention uses an electrospinning method to make a first spinning membrane with a fiber structure from a first polymer and sodium silicate, and a second polymer and a phase change flame retardant material to make a second spinning membrane with a fiber structure, and uses a hot pressing method to compound the two, so that the first spinning membrane forms a first membrane layer and the second spinning membrane forms a second membrane layer, so that the fibers can be fused to increase the mechanical strength of the membrane, thereby obtaining a double-layer composite membrane. The membrane obtained by this method has a high porosity and good pore uniformity. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 These are SEM images of the first membrane layer and the second membrane layer in the double-layer composite membrane of Example 1, wherein (a) corresponds to the first membrane layer; and (b) corresponds to the second membrane layer. DETAILED DESCRIPTION
[0042] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementation methods.
[0043] The specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0044] In one embodiment, the present invention provides a double-layer composite diaphragm, which includes a first membrane layer and a second membrane layer that are stacked, the first membrane layer includes a first fiber skeleton, the first fiber skeleton includes a mixture, the mixture includes sodium silicate and a first polymer, the second membrane layer includes a second fiber skeleton, the second fiber skeleton includes second polymer fibers, and the second polymer fibers are partially wrapped with a phase change flame retardant material to form a necklace structure.
[0045] The double-layer composite diaphragm provided by one embodiment of the present invention has good electrochemical performance, good safety performance and excellent effect of reducing the probability of thermal runaway. The specific reasons are as follows: (I) Both the first film layer and the second film layer include a fiber skeleton structure, which can provide a high porosity, thereby having an excellent electrolyte retention rate. At the same time, the high porosity makes the diaphragm have a high ion pass rate, which promotes Li + It is uniformly deposited on the negative electrode side to form a stable SEI film, which is beneficial to improving the electrochemical performance of the battery; (II) Sodium silicate has a high elastic modulus, is not easy to shrink at high temperature, and has good insulation. Sodium silicate and the first polymer are used to construct the first film layer. The hydrogen bond between the two makes the diaphragm have a higher Young's modulus, which exceeds the Young's modulus of metallic lithium, and can inhibit the growth of lithium dendrites, thereby physically preventing the growth and spread of lithium dendrites; at the same time, the battery system is prone to lithium salt decomposition under conditions of excessive water content or improper use to produce hydrofluoric acid that can corrode electrodes and current collectors. Sodium silicate can react with hydrofluoric acid, and sodium silicate with Lewis base effect can neutralize the harmful hydrofluoric acid in the system, thereby protecting the stable operation of the battery; in addition, the high heat resistance and low shrinkage of the first film layer ensure that the positive and negative electrodes will not be in direct contact, reducing the scale of thermal runaway; (III) Because the phase change flame retardant material is firmly wrapped by the second polymer fiber, a necklace structure is formed (see Figure 1 The red box in the figure shows that when a certain temperature is reached, the phase change flame retardant material melts (for example, the Fe3P material melts at 1100°C) and absorbs heat, which can fully guarantee the safety characteristics of the battery and inhibit thermal runaway. At the same time, since the phase change flame retardant material is in a wrapped state, it avoids direct contact between the phase change flame retardant material and lithium metal to cause unnecessary side reactions. Furthermore, when thermal runaway occurs, the first polymer and / or the second polymer melts to form a closed-cell structure, cutting off the lithium ion transmission path.
[0046] Compared with the commercially available Celgard membrane, the double-layer composite membrane of the present invention has many characteristics such as environmental protection, high thermal stability, good electrolyte affinity, excellent electrochemical performance, and good effect in reducing the probability of thermal runaway, and shows good application prospects in lithium metal batteries.
[0047] In one embodiment, the thickness of the first film layer is A, the thickness of the second film layer is B, and 1 / 3≤A / (A+B)≤2 / 3. Among them, A / (A+B) reflects the thickness ratio of the first film layer relative to the total thickness of the first film layer and the second film layer. If this relationship is met, the probability of thermal runaway can be better reduced. If the thickness ratio of the first film layer is too small, the ability to resist shrinkage will decrease; at the same time, since this layer has a high elastic modulus and mechanical strength, if the thickness ratio of the first film layer is too large, it will increase the brittleness of the diaphragm, which is not conducive to practical application.
[0048] In one embodiment, the phase change flame retardant material includes at least one of Fe3P, (NH4)2·HPO4, (NH4)·H2PO4, aluminum hydroxide, magnesium hydroxide, red phosphorus, ammonium polyphosphate, zinc borate and antimony oxide, preferably Fe3P and / or aluminum oxide. Fe3P and aluminum oxide have low surface energy, which can promote the infiltration of electrode liquid and improve the wetting effect of the diaphragm.
[0049] In one embodiment, the phase change flame retardant material is Fe3P. When Fe3P is used as the phase change flame retardant material, the necklace structure formed by Fe3P particles being wrapped by the second polymer can better promote electrolyte infiltration and rapid ion transfer.
[0050] Since polymer materials have good mechanical properties, flexibility and chemical stability, and can be electrospun and hot-pressed to form a membrane that meets the porous performance requirements, the first polymer and the second polymer in the present invention can use common polymer materials to achieve the basic performance requirements.
[0051] In one embodiment, the first polymer includes at least one of polyvinyl alcohol (PVA), polyvinylidene fluoride (PVDF), polypropylene (PP), polyethylene (PE), polyethylene terephthalate (PET), polymethyl methacrylate (PMMA) and polyethylene oxide (PEO), preferably PVA, which has low surface energy and good flexibility. Using it to prepare the diaphragm is beneficial to improving the performance of the diaphragm.
[0052] In one embodiment, the second polymer includes at least one of polyvinyl alcohol, polyvinylidene fluoride, polypropylene, polyethylene, polyethylene terephthalate, polymethyl methacrylate and polyethylene oxide, preferably PVA, which has low surface energy and good flexibility. Using it to prepare the diaphragm is beneficial to improving the performance of the diaphragm.
[0053] In the embodiment of the present invention, the first polymer and the second polymer may be of the same type or different types, which is not specifically limited in the present invention.
[0054] In one embodiment, the melting temperature of the first polymer is t1, the melting temperature of the second polymer is t2, the melting temperature of the phase change flame retardant material is t3, and the melting temperature of the sodium silicate is t4, t1< t3< t4, t2< t3< t4. In this case, when the melting temperature of the first polymer / or the second polymer is exceeded, the first polymer and / or the second polymer melts first, and at the same time blocks the ion transmission path. When thermal runaway occurs at a higher temperature, the phase change flame retardant material melts and absorbs heat, reducing the peak temperature of thermal runaway.
[0055] In one embodiment, the mass proportion of the sodium silicate in the first film layer is 33.3%-50.0%, for example, 33.3%, 33.5%, 34.0%, 34.5%, 35.0%, 36.0%, 36.5%, 37.0%, 38.0%, 39.0%, 40.0%, 41.0%, 42.0%, 43.0%, 44.0%, 45.0%, 46.0%, 47.0%, 47.5%, 48.0%, 49.0% or 50.0%, etc. If the proportion of sodium silicate is too high, the material flexibility is poor; if the proportion of sodium silicate is too low, the effect of absorbing liquid to prevent thermal shrinkage is poor.
[0056] In one embodiment, the mass proportion of the phase change flame retardant material in the second film layer is 20.0%-50.0%, for example, it can be 20.0%, 20.5%, 21.0%, 21.5%, 22.0%, 23.0%, 23.5%, 24.0%, 25.0%, 26.0%, 27.0%, 28.0%, 29.0%, 30.0%, 31.0%, 32.0%, 33.0%, 33.5%, 34.0%, 34.5%, 35.0%, 36.0%, 36.5%, 37.0%, 38.0%, 39.0%, 40.0%, 41.0%, 42.0%, 43.0%, 44.0%, 45.0%, 46.0%, 47.0%, 47.5%, 48.0%, 49.0% or 50.0%, etc. If the proportion of phase change flame retardant material is too high, the material flexibility will be poor; if the proportion of phase change flame retardant material is too low, the flame retardant effect will be poor.
[0057] In one embodiment, the porosity of the double-layer composite membrane is 37%-46%, for example, 37%, 37.5%, 38%, 38.5%, 39%, 39.5%, 40%, 40.5%, 41%, 41.5%, 42%, 42.5%, 43%, 43.5%, 44%, 44.5%, 45%, 45.5% or 46%, etc. The high porosity allows the membrane to have a high ion pass rate, promoting Li + It is uniformly deposited on the anode side to form a stable SEI film, which is beneficial to improving the electrochemical performance of the battery; at the same time, the high porosity is beneficial to improving the electrolyte retention rate of the diaphragm.
[0058] In another embodiment, the present invention provides a method for preparing the double-layer composite diaphragm as described above, comprising the following steps:
[0059] (1) Providing electrospinning solution:
[0060] adding sodium silicate to the first polymer glue to obtain a first solution;
[0061] Adding a phase change flame retardant material to the second polymer glue to obtain a second solution;
[0062] (2) Electrospinning:
[0063] Electrospinning is performed using the first solution and the second solution respectively to obtain a first spinning membrane and a second spinning membrane;
[0064] (3) Hot pressing treatment:
[0065] The first spinning membrane and the second spinning membrane are stacked together and hot pressed to obtain the double-layer composite membrane, wherein the double-layer composite membrane includes a first membrane layer and a second membrane layer stacked together, wherein the first spinning membrane forms the first membrane layer and the second spinning membrane forms the second membrane layer. Electrospinning is a special fiber manufacturing process in which a polymer solution is jet-spun in a strong electric field, which can form fiber filaments with a diameter of nanometers and constitute a fiber skeleton.
[0066] One embodiment of the present invention uses an electrospinning method to make a first polymer and sodium silicate into a first spinning membrane with a fiber structure, and a second polymer and a phase change flame retardant material into a second spinning membrane with a fiber structure, and the two are compounded by a hot pressing method, the first spinning membrane forms a first membrane layer, and the second spinning membrane forms a second membrane layer, so that the fibers can be fused to increase the mechanical strength of the membrane, and a double-layer composite membrane can be obtained. The membrane prepared by this method has a high porosity and good uniformity of pores. If the electrospinning method is replaced by other methods, it will result in the inability to form the fiber structure of the present invention.
[0067] In one embodiment, the viscosity of the first polymer glue in step (1) is μ1, 50cP≤μ1≤20000cP, wherein μ1 can be, for example, 50cP, 100cP, 200cP, 500cP, 800cP, 1000cP, 1500cP, 2000cP, 2500cP, 3000cP, 4000cP, 5000cP, 6000cP, 8000cP, 10000cP, 12000cP, 15000cP, 17000cP or 20000cP, etc.
[0068] In one embodiment, after the sodium silicate is added, heating and stirring are performed to form a first solution in a gel state.
[0069] In one embodiment, the viscosity of the first solution in step (1) is μ2, 50 cP≤μ2≤30000 cP, wherein μ2 can be, for example, 50 cP, 100 cP, 200 cP, 500 cP, 800 cP, 1000 cP, 1500 cP, 2000 cP, 2500 cP, 3000 cP, 4000 cP, 5000 cP, 6000 cP, 8000 cP, 10000 cP, 12000 cP, 15000 cP, 17000 cP, 20000 cP, 22000 cP, 24000 cP, 26000 cP, 28000 cP or 30000 cP, etc.
[0070] In one embodiment, the viscosity of the second polymer glue in step (1) is μ3, 50cP≤μ3≤20000cP, wherein μ3 can be, for example, 50cP, 100cP, 200cP, 500cP, 800cP, 1000cP, 1500cP, 2000cP, 2500cP, 3000cP, 4000cP, 5000cP, 6000cP, 8000cP, 10000cP, 12000cP, 15000cP, 17000cP or 20000cP, etc.
[0071] In one embodiment, after the phase change flame retardant material is added, heating and stirring are performed to form a second solution in a gel state.
[0072] In one embodiment, the viscosity of the second solution in step (1) is μ4, 50 cP≤μ4≤30000 cP, wherein μ4 can be, for example, 50 cP, 100 cP, 200 cP, 500 cP, 800 cP, 1000 cP, 1500 cP, 2000 cP, 2500 cP, 3000 cP, 4000 cP, 5000 cP, 6000 cP, 8000 cP, 10000 cP, 12000 cP, 15000 cP, 17000 cP, 20000 cP, 22000 cP, 24000 cP, 26000 cP, 28000 cP or 30000 cP, etc.
[0073] In one embodiment, in step (1), the phase change flame retardant material is pre-milled to a particle size of 0.1 μm-1 μm, for example, 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm or 1 μm. If the particle size of the phase change flame retardant material is too large, it cannot be in close contact to achieve an effective flame retardant effect, and even the phase change flame retardant material cannot be completely wrapped; if the particle size of the phase change flame retardant material is too small, it will affect the electrolyte infiltration and lithium ion permeability.
[0074] In one embodiment, in step (2), the volume V1 of the first solution and the volume V2 of the second solution satisfy: 1 / 3≤V2 / (V2+V1)≤2 / 3.
[0075] In one embodiment, the temperature of the hot pressing in step (3) is 80°C-220°C, for example, it can be 80°C, 85°C, 90°C, 95°C, 100°C, 110°C, 120°C, 130°C, 140°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C or 220°C, etc.
[0076] In one embodiment, the hot pressing pressure in step (3) is 10 kPa-30 kPa, for example, 10 kPa, 11 kPa, 12 kPa, 14 kPa, 15 kPa, 17 kPa, 18 kPa, 20 kPa, 22 kPa, 23 kPa, 25 kPa, 27 kPa, 28 kPa or 30 kPa, etc.
[0077] If the temperature and pressure of the hot pressing are too high, the second spinning membrane may be damaged; if the temperature and pressure of the hot pressing are too low, the first spinning membrane and the second spinning membrane cannot be well combined into a double-layer composite membrane.
[0078] In one embodiment, the hot pressing time in step (3) is 0.5h-10h, for example, it can be 0.5h, 1h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, 8h, 8.5h, 9h or 10h.
[0079] In another embodiment, the present invention provides a battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the separator adopts the above-mentioned double-layer composite separator or a double-layer composite separator prepared by the above-mentioned method, wherein the first film layer is arranged close to the negative electrode, and the second film layer is arranged close to the positive electrode.
[0080] In the implementation manner of the present invention, it is necessary to arrange the first film layer close to the negative electrode and the second film layer close to the positive electrode. This is because: the second film layer contains phase change flame retardant materials, and some phase change flame retardant materials are conductive. The phase change flame retardant materials may not be completely wrapped, and it is necessary to use the insulation of the first film layer to separate them; if some phase change flame retardant materials (such as Fe3P) are arranged close to the negative electrode, they will react with lithium ions from the positive electrode at low potential, so the second film layer containing them should be arranged close to the positive electrode.
[0081] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0082] The following are typical but non-limiting examples:
[0083] Example 1
[0084] The present embodiment provides a double-layer composite diaphragm, comprising a first membrane layer and a second membrane layer stacked together, the first membrane layer comprising a first fiber skeleton, the first fiber skeleton comprising a mixture, the mixture comprising sodium silicate and a first polymer, the second membrane layer comprising a second fiber skeleton, the second fiber skeleton comprising second polymer fibers, the second polymer fibers are partially wrapped with a phase change flame retardant material to form a necklace structure, wherein the phase change flame retardant material is Fe3P, the first polymer and the second polymer are both polyvinyl alcohol (PVA), the mass proportion of sodium silicate in the first membrane layer is 45%, and the mass proportion of the phase change flame retardant material in the second membrane layer is 45%.
[0085] This embodiment also provides a method for preparing the above-mentioned double-layer composite diaphragm, comprising the following steps:
[0086] 1. Preparation of Fe3P@PVA composite membrane
[0087] 4 g of polyvinyl alcohol and 36 ml of deionized water were placed in a tightly sealed glass bottle, which was placed in a 90°C oven for about 3 hours. When the polyvinyl alcohol became transparent, it was taken out and magnetically stirred to completely dissolve it for spinning. The mass fraction of polyvinyl alcohol was controlled to be 10%.
[0088] 2 g of Fe3P powder was added to a ball mill beaker and ball milled at 400 rpm for 3 h to make the Fe3P particle size 0.5 μm. The ball milled Fe3P was evenly dispersed in anhydrous ethanol by ultrasonic treatment. Then the Fe3P suspension was slowly added dropwise to the above polyvinyl alcohol solution, stirred and mixed to form a uniform suspension, and ultrasonic defoaming treatment was performed before spinning.
[0089] Next, the mixed solution was loaded into a disposable syringe, mounted on an electrospinning push rod, the positive voltage was adjusted to 15 kV, the feed rate was set to 0.1 ml / min, and the solution was converted into a composite fiber membrane, namely the Fe3P@PVA composite membrane, by electrospinning.
[0090] 2. Preparation of NaSiO3@PVA composite membrane
[0091] 4 g of polyvinyl alcohol and 36 ml of deionized water were placed in a tightly sealed glass bottle, which was placed in a 90°C oven for about 3 hours. When the polyvinyl alcohol became transparent, it was taken out and magnetically stirred to completely dissolve it for spinning. The mass fraction of polyvinyl alcohol was controlled to be 10%.
[0092] Take 2g NaSiO3 and disperse it evenly in 5ml deionized water. Then slowly add the NaSiO3 suspension to the above polyvinyl alcohol solution, stir and mix to form a uniform milky white viscous solution, and ultrasonic defoaming treatment for spinning. Next, the above mixed solution is loaded into a disposable syringe, installed on the electrospinning push rod, the positive voltage is adjusted to 15kV, the feed rate is set to 0.1ml / min, and the solution is converted into a composite fiber diaphragm by electrospinning, that is, a NaSiO3@PVA composite diaphragm.
[0093] 3. Preparation of double-layer composite membrane
[0094] The Fe3P@PVA composite membrane (thickness B) and the NaSiO3@PVA composite membrane (thickness A) are placed in upper and lower layers with a thickness ratio of A / B of 1:1, then A / (A+B)=1:2. The fiber separator is placed in an oven and heat treated at 200°C for 30 minutes under a pressure of 20 kPa to allow the fibers to fuse and increase the mechanical strength of the fiber membrane. The prepared membrane is a double-layer composite membrane.
[0095] Figure 1 The SEM images of the first and second membrane layers in the double-layer composite diaphragm of Example 1, where (a) corresponds to the first membrane layer; (b) corresponds to the second membrane layer. It can be seen from the figure that the spinning of the first membrane layer is uniform and fine, forming a fiber skeleton structure, and the sodium silicate and PVA are well mixed; the spinning of the second membrane layer is uniform and fine, and the PVA partially wraps the Fe3P particles to form a necklace structure (see the red frame in the figure), the Fe3P particles are evenly dispersed, and each Fe3P particle is wrapped by PVA. This structure can promote electrolyte infiltration and rapid ion transfer, and enhance rate performance. In addition, Fe3P, as a phase change flame retardant material, can melt and absorb heat when thermal runaway occurs, delaying the time of thermal runaway and reducing the peak temperature, thereby inhibiting thermal runaway.
[0096] Example 2
[0097] The present embodiment provides a double-layer composite diaphragm, comprising a first membrane layer and a second membrane layer stacked in layers, the first membrane layer comprising a first fiber skeleton, the first fiber skeleton comprising a mixture, the mixture comprising sodium silicate and a first polymer, the second membrane layer comprising a second fiber skeleton, the second fiber skeleton comprising second polymer fibers, the second polymer fibers are partially wrapped with a phase change flame retardant material to form a necklace structure, wherein the phase change flame retardant material is Fe3P, the first polymer and the second polymer are both polyvinyl alcohol, the mass proportion of sodium silicate in the first membrane layer is 45.0%, and the mass proportion of the phase change flame retardant material in the second membrane layer is 50.0%.
[0098] This embodiment also provides a method for preparing the above-mentioned double-layer composite diaphragm, comprising the following steps:
[0099] 1. Preparation of Fe3P@PVA composite membrane
[0100] Take 2g of polyvinyl alcohol and 36ml of deionized water and put them into a tightly sealed glass bottle, put it into a 90°C oven for about 3h, take it out when the polyvinyl alcohol becomes transparent, and stir it magnetically to make it completely dissolved for spinning. The mass fraction of polyvinyl alcohol is controlled to be 5%.
[0101] 2 g of Fe3P powder was added to a ball mill beaker and ball milled at 400 rpm for 3 h to make the Fe3P particle size 0.5 μm. The ball milled Fe3P was evenly dispersed in anhydrous ethanol by ultrasonic treatment. Then the Fe3P suspension was slowly added dropwise to the above polyvinyl alcohol solution, stirred and mixed to form a uniform suspension, and ultrasonic defoaming treatment was performed before spinning.
[0102] Next, the mixed solution was loaded into a disposable syringe, mounted on an electrospinning push rod, the positive voltage was adjusted to 15 kV, the feed rate was set to 0.05 ml / min, and the solution was converted into a composite fiber membrane, i.e., the Fe3P@PVA composite membrane, by electrospinning.
[0103] 2. Preparation of NaSiO3@PVA composite membrane
[0104] 4 g of polyvinyl alcohol and 36 ml of deionized water were placed in a tightly sealed glass bottle, which was placed in a 90°C oven for about 3 hours. When the polyvinyl alcohol became transparent, it was taken out and magnetically stirred to completely dissolve it for spinning. The mass fraction of polyvinyl alcohol was controlled to be 10%.
[0105] Take 2g NaSiO3 and disperse it evenly in 5ml deionized water. Then slowly add the NaSiO3 suspension to the above polyvinyl alcohol solution, stir and mix to form a uniform milky white viscous solution, and ultrasonic defoaming treatment for spinning. Next, the above mixed solution is loaded into a disposable syringe, installed on the electrospinning push rod, the positive voltage is adjusted to 15kV, the feed rate is set to 0.1ml / min, and the solution is converted into a composite fiber diaphragm by electrospinning, that is, a NaSiO3@PVA composite diaphragm.
[0106] 3. Preparation of double-layer composite membrane
[0107] The Fe3P@PVA composite membrane (thickness B) and the NaSiO3@PVA composite membrane (thickness A) are placed in upper and lower layers with a thickness ratio of A / B of 1:2, then A / (A+B)=1:3. The fiber separator is placed in an oven and heat treated at 200°C for 30 minutes under a pressure of 20 kPa to allow the fibers to fuse and increase the mechanical strength of the fiber membrane. The prepared membrane is a double-layer composite membrane.
[0108] Example 3
[0109] The present embodiment provides a double-layer composite diaphragm, comprising a first membrane layer and a second membrane layer stacked in layers, the first membrane layer comprising a first fiber skeleton, the first fiber skeleton comprising a mixture, the mixture comprising sodium silicate and a first polymer, the second membrane layer comprising a second fiber skeleton, the second fiber skeleton comprising second polymer fibers, the second polymer fibers are partially wrapped with a phase change flame retardant material to form a necklace structure, wherein the phase change flame retardant material is Fe3P, the first polymer and the second polymer are both polyvinyl alcohol, the mass proportion of sodium silicate in the first membrane layer is 45.0%, and the mass proportion of the phase change flame retardant material in the second membrane layer is 35.0%.
[0110] This embodiment also provides a method for preparing the above-mentioned double-layer composite diaphragm, comprising the following steps:
[0111] 1. Preparation of Fe3P@PVA composite membrane
[0112] 8 g of polyvinyl alcohol and 36 ml of deionized water were placed in a tightly sealed glass bottle, which was placed in a 90°C oven for about 3 hours. When the polyvinyl alcohol became transparent, it was taken out and magnetically stirred to completely dissolve it for spinning. The mass fraction of polyvinyl alcohol was controlled to be 20%.
[0113] 2 g of Fe3P powder was added to a ball mill beaker and ball milled at 400 rpm for 3 h to make the Fe3P particle size 0.5 μm. The ball milled Fe3P was evenly dispersed in anhydrous ethanol by ultrasonic treatment. Then the Fe3P suspension was slowly added dropwise to the above polyvinyl alcohol solution, stirred and mixed to form a uniform suspension, and ultrasonic defoaming treatment was performed before spinning.
[0114] Next, the mixed solution was loaded into a disposable syringe, mounted on an electrospinning push rod, the positive voltage was adjusted to 15 kV, the feed rate was set to 0.2 ml / min, and the solution was converted into a composite fiber membrane, i.e., the Fe3P@PVA composite membrane, by electrospinning.
[0115] 2. Preparation of NaSiO3@PVA composite membrane
[0116] 4 g of polyvinyl alcohol and 36 ml of deionized water were placed in a tightly sealed glass bottle, which was placed in a 90°C oven for about 3 hours. When the polyvinyl alcohol became transparent, it was taken out and magnetically stirred to completely dissolve it for spinning. The mass fraction of polyvinyl alcohol was controlled to be 10%.
[0117] Take 2g NaSiO3 and disperse it evenly in 5ml deionized water. Then slowly add the NaSiO3 suspension to the above polyvinyl alcohol solution, stir and mix to form a uniform milky white viscous solution, and ultrasonic defoaming treatment for spinning. Next, the above mixed solution is loaded into a disposable syringe, installed on the electrospinning push rod, the positive voltage is adjusted to 15kV, the feed rate is set to 0.1ml / min, and the solution is converted into a composite fiber diaphragm by electrospinning, that is, a NaSiO3@PVA composite diaphragm.
[0118] 3. Preparation of double-layer composite membrane
[0119] The Fe3P@PVA composite membrane (thickness B) and the NaSiO3@PVA composite membrane (thickness A) are placed in upper and lower layers with a thickness ratio of A / B of 2:1, then A / (A+B)=2:3. The fiber separator is placed in an oven and heat treated at 200°C for 30 minutes under a pressure of 20 kPa to allow the fibers to fuse and increase the mechanical strength of the fiber membrane. The prepared membrane is a double-layer composite membrane.
[0120] Example 4
[0121] The present embodiment provides a double-layer composite diaphragm, comprising a first membrane layer and a second membrane layer stacked in layers, the first membrane layer comprising a first fiber skeleton, the first fiber skeleton comprising a mixture, the mixture comprising sodium silicate and a first polymer, the second membrane layer comprising a second fiber skeleton, the second fiber skeleton comprising second polymer fibers, the second polymer fibers are partially wrapped with a phase change flame retardant material to form a necklace structure, wherein the phase change flame retardant material is Fe3P, the first polymer and the second polymer are both polyvinyl alcohol, the mass proportion of sodium silicate in the first membrane layer is 50.0%, and the mass proportion of the phase change flame retardant material in the second membrane layer is 45.0%.
[0122] This embodiment also provides a method for preparing the above-mentioned double-layer composite diaphragm, comprising the following steps:
[0123] 1. Preparation of Fe3P@PVA composite membrane
[0124] 4 g of polyvinyl alcohol and 36 ml of deionized water were placed in a tightly sealed glass bottle, which was placed in a 90°C oven for about 3 hours. When the polyvinyl alcohol became transparent, it was taken out and magnetically stirred to completely dissolve it for spinning. The mass fraction of polyvinyl alcohol was controlled to be 10%.
[0125] 2 g of Fe3P powder was added to a ball mill beaker and ball milled at 400 rpm for 3 h to make the Fe3P particle size 0.5 μm. The ball milled Fe3P was evenly dispersed in anhydrous ethanol by ultrasonic treatment. Then the Fe3P suspension was slowly added dropwise to the above polyvinyl alcohol solution, stirred and mixed to form a uniform suspension, and ultrasonic defoaming treatment was performed before spinning.
[0126] Next, the mixed solution was loaded into a disposable syringe, mounted on an electrospinning push rod, the positive voltage was adjusted to 15 kV, the feed rate was set to 0.1 ml / min, and the solution was converted into a composite fiber membrane, namely the Fe3P@PVA composite membrane, by electrospinning.
[0127] 2. Preparation of NaSiO3@PVA composite membrane
[0128] Take 2g of polyvinyl alcohol and 36ml of deionized water and put them into a tightly sealed glass bottle, put it into a 90°C oven for about 3h, take it out when the polyvinyl alcohol becomes transparent, and stir it magnetically to make it completely dissolved for spinning. The mass fraction of polyvinyl alcohol is controlled to be 5%.
[0129] Take 2g NaSiO3 and disperse it evenly in 5ml deionized water. Then slowly add the NaSiO3 suspension to the above polyvinyl alcohol solution, stir and mix to form a uniform milky white viscous solution, and ultrasonic defoaming treatment for spinning. Next, the above mixed solution is loaded into a disposable syringe, installed on the electrospinning push rod, the positive voltage is adjusted to 15kV, the feed rate is set to 0.05ml / min, and the solution is converted into a composite fiber diaphragm by electrospinning, that is, a NaSiO3@PVA composite diaphragm.
[0130] 3. Preparation of double-layer composite membrane
[0131] The Fe3P@PVA composite membrane (thickness B) and the NaSiO3@PVA composite membrane (thickness A) are placed in upper and lower layers with a thickness ratio of A / B of 2:1, then A / (A+B)=2:3. The fiber separator is placed in an oven and heat treated at 200°C for 30 minutes under a pressure of 20 kPa to allow the fibers to fuse and increase the mechanical strength of the fiber membrane. The prepared membrane is a double-layer composite membrane.
[0132] Example 5
[0133] The present embodiment provides a double-layer composite diaphragm, comprising a first membrane layer and a second membrane layer stacked together, the first membrane layer comprising a first fiber skeleton, the first fiber skeleton comprising a mixture, the mixture comprising sodium silicate and a first polymer, the second membrane layer comprising a second fiber skeleton, the second fiber skeleton comprising second polymer fibers, the second polymer fibers are partially wrapped with a phase change flame retardant material to form a necklace structure, wherein the phase change flame retardant material is Fe3P, the first polymer and the second polymer are both polyvinyl alcohol (PVA), the mass proportion of sodium silicate in the first membrane layer is 35.0%, and the mass proportion of the phase change flame retardant material in the second membrane layer is 45.0%.
[0134] This embodiment also provides a method for preparing the above-mentioned double-layer composite diaphragm, comprising the following steps:
[0135] 1. Preparation of Fe3P@PVA composite membrane
[0136] 4 g of polyvinyl alcohol and 36 ml of deionized water were placed in a tightly sealed glass bottle, which was placed in a 90°C oven for about 3 hours. When the polyvinyl alcohol became transparent, it was taken out and magnetically stirred to completely dissolve it for spinning. The mass fraction of polyvinyl alcohol was controlled to be 10%.
[0137] 2 g of Fe3P powder was added to a ball mill beaker and ball milled at 400 rpm for 3 h to make the Fe3P particle size 0.5 μm. The ball milled Fe3P was evenly dispersed in anhydrous ethanol by ultrasonic treatment. Then the Fe3P suspension was slowly added dropwise to the above polyvinyl alcohol solution, stirred and mixed to form a uniform suspension, and ultrasonic defoaming treatment was performed before spinning.
[0138] Next, the mixed solution was loaded into a disposable syringe, mounted on an electrospinning push rod, the positive voltage was adjusted to 15 kV, the feed rate was set to 0.1 ml / min, and the solution was converted into a composite fiber membrane, namely the Fe3P@PVA composite membrane, by electrospinning.
[0139] 2. Preparation of NaSiO3@PVA composite membrane
[0140] 8 g of polyvinyl alcohol and 36 ml of deionized water were placed in a tightly sealed glass bottle, which was placed in a 90°C oven for about 3 hours. When the polyvinyl alcohol became transparent, it was taken out and magnetically stirred to completely dissolve it for spinning. The mass fraction of polyvinyl alcohol was controlled to be 20%.
[0141] Take 2g NaSiO3 and disperse it evenly in 5ml deionized water. Then slowly add the NaSiO3 suspension to the above polyvinyl alcohol solution, stir and mix to form a uniform milky white viscous solution, and ultrasonic defoaming treatment for spinning. Next, the above mixed solution is loaded into a disposable syringe, installed on the electrospinning push rod, the positive voltage is adjusted to 15kV, the feed rate is set to 0.2ml / min, and the solution is converted into a composite fiber diaphragm by electrospinning, that is, a NaSiO3@PVA composite diaphragm.
[0142] 3. Preparation of double-layer composite membrane
[0143] The Fe3P@PVA composite membrane (thickness B) and the NaSiO3@PVA composite membrane (thickness A) are placed in upper and lower layers with a thickness ratio of A / B of 1:2, then A / (A+B)=1:3. The fiber separator is placed in an oven and heat treated at 200°C for 30 minutes under a pressure of 20 kPa to allow the fibers to fuse and increase the mechanical strength of the fiber membrane. The prepared membrane is a double-layer composite membrane.
[0144] Example 6
[0145] The present embodiment provides a double-layer composite diaphragm, comprising a first membrane layer and a second membrane layer stacked in layers, the first membrane layer comprising a first fiber skeleton, the first fiber skeleton comprising a mixture, the mixture comprising sodium silicate and a first polymer, the second membrane layer comprising a second fiber skeleton, the second fiber skeleton comprising second polymer fibers, the second polymer fibers are partially wrapped with a phase change flame retardant material to form a necklace structure, wherein the phase change flame retardant material is Fe3P, the first polymer and the second polymer are both polyethylene oxide, the mass proportion of sodium silicate in the first membrane layer is 45.0%, and the mass proportion of the phase change flame retardant material in the second membrane layer is 45.0%.
[0146] This embodiment also provides a method for preparing the above-mentioned double-layer composite diaphragm, comprising the following steps:
[0147] 1. Preparation of Fe3P@PEO composite membrane
[0148] Take 4g of polyethylene oxide and 36ml of deionized water and put them into a tightly sealed glass bottle, put it into a 90°C oven for about 3h, take it out when the polyethylene oxide becomes transparent, and stir it magnetically to make it completely dissolved for spinning. The mass fraction of polyethylene oxide is controlled to be 10%.
[0149] 2 g of Fe3P powder was added to a ball mill beaker and ball milled at 400 rpm for 3 h to make the Fe3P particle size 0.5 μm. The ball milled Fe3P was evenly dispersed in anhydrous ethanol by ultrasonic treatment. Then the Fe3P suspension was slowly added dropwise to the polyethylene oxide solution, stirred and mixed to form a uniform suspension, and ultrasonic defoaming treatment was performed before spinning.
[0150] Next, the mixed solution was loaded into a disposable syringe, mounted on an electrospinning push rod, the positive voltage was adjusted to 15 kV, the feed rate was set to 0.1 ml / min, and the solution was converted into a composite fiber membrane, namely the Fe3P@PVA composite membrane, by electrospinning.
[0151] 2. Preparation of NaSiO3@PEO composite membrane
[0152] 4 g of polyethylene oxide and 36 ml of toluene were placed in a tightly sealed glass bottle, which was placed in a 90°C oven for about 3 hours. When the polyethylene oxide became transparent, it was taken out and magnetically stirred to completely dissolve it for spinning. The mass fraction of polyethylene oxide was controlled to be 10%.
[0153] Take 2g NaSiO3 and disperse it evenly in 5ml deionized water. Then slowly add the NaSiO3 suspension to the above polyethylene oxide solution, stir and mix to form a uniform milky white viscous solution, and ultrasonic defoaming treatment for spinning. Next, the above mixed solution is loaded into a disposable syringe, installed on the electrospinning push rod, the positive voltage is adjusted to 15kV, the feed rate is set to 0.1ml / min, and the solution is converted into a composite fiber diaphragm by electrospinning, that is, a NaSiO3@PEO composite diaphragm.
[0154] 3. Preparation of double-layer composite membrane
[0155] The Fe3P@PEO composite membrane (thickness B) and the NaSiO3@PEO composite membrane (thickness A) are placed in upper and lower layers with a thickness ratio of A / B of 1:1, then A / (A+B)=1:2. The fiber separator is placed in an oven and heat treated at 200°C for 30 minutes under a pressure of 20 kPa to allow the fibers to fuse and increase the mechanical strength of the fiber membrane. The prepared membrane is a double-layer composite membrane.
[0156] Example 7
[0157] The difference between this embodiment and Embodiment 1 is that the sum of the thickness A of the first film layer and the thickness B of the second film layer remains unchanged, and A / (A+B) is 1 / 4.
[0158] Example 8
[0159] The difference between this embodiment and embodiment 1 is that the sum of the thickness A of the first film layer and the thickness B of the second film layer remains unchanged, and A / (A+B) is 3 / 4.
[0160] Example 9
[0161] The present embodiment provides a double-layer composite diaphragm, comprising a first membrane layer and a second membrane layer stacked together, the first membrane layer comprising a first fiber skeleton, the first fiber skeleton comprising a mixture, the mixture comprising sodium silicate and a first polymer, the second membrane layer comprising a second fiber skeleton, the second fiber skeleton comprising second polymer fibers, the second polymer fibers are partially wrapped with a phase change flame retardant material to form a necklace structure, wherein the phase change flame retardant material is aluminum hydroxide, the first polymer is polypropylene, the second polymer is polymethyl methacrylate, the mass proportion of sodium silicate in the first membrane layer is 50.0%, and the mass proportion of the phase change flame retardant material in the second membrane layer is 50.0%.
[0162] This embodiment also provides a method for preparing the above-mentioned double-layer composite diaphragm, comprising the following steps:
[0163] 1. Preparation of Al(OH)3@PMMA composite membrane
[0164] 5 g of polymethyl methacrylate and 36 ml of acetone were placed in a tightly sealed glass bottle, which was placed in an 80°C oven for about 3 hours. When the polymethyl methacrylate became transparent, it was taken out and magnetically stirred to completely dissolve it for spinning. The mass fraction of polymethyl methacrylate was controlled to be 12.5%.
[0165] Take 3g of aluminum hydroxide powder and add it to a ball mill beaker. Ball mill at 300rpm for 5h to make the aluminum hydroxide particle size 0.3μm. The aluminum hydroxide after ball milling is evenly dispersed in anhydrous ethanol by ultrasonic treatment. Then slowly add the aluminum hydroxide suspension to the above polymethyl methacrylate solution, stir and mix to form a uniform suspension, and ultrasonic defoaming treatment before spinning.
[0166] Next, the mixed solution was loaded into a disposable syringe and mounted on an electrospinning push rod. The positive voltage was adjusted to 12 kV and the feed rate was set to 0.15 ml / min. The solution was converted into a composite fiber membrane, i.e., Al(OH)3@PMMA composite membrane, by electrospinning.
[0167] 2. Preparation of NaSiO3@PP composite membrane
[0168] 7 g of polypropylene and 36 ml of deionized water were placed in a tightly sealed glass bottle, which was placed in a 95°C oven for 2 h. When the polypropylene became transparent, it was taken out and magnetically stirred to completely dissolve it for spinning. The mass fraction of polypropylene was controlled to be 17.5%.
[0169] Take 6g NaSiO3 and disperse it evenly in 5ml deionized water. Then slowly add the NaSiO3 suspension to the above polypropylene solution, stir and mix to form a uniform milky white viscous solution, and ultrasonic defoaming treatment for spinning. Next, the above mixed solution is loaded into a disposable syringe, installed on the electrospinning push rod, the positive voltage is adjusted to 18kV, the feed rate is set to 0.3ml / min, and the solution is converted into a composite fiber diaphragm by electrospinning, that is, a NaSiO3@PP composite diaphragm.
[0170] 3. Preparation of double-layer composite membrane
[0171] Place the Al(OH)3@PMMA composite membrane (thickness B) and the NaSiO3@PP composite membrane (thickness A) in upper and lower layers with a thickness ratio of A / B of 1:1.5, then A / (A+B)=1:2.5. Put the fiber separator into an oven and heat treat it at 100°C for 6 hours under a pressure of 10 kPa to allow the fibers to fuse and increase the mechanical strength of the fiber membrane. The prepared membrane is a double-layer composite membrane.
[0172] Example 10
[0173] The present embodiment provides a double-layer composite diaphragm, comprising a first membrane layer and a second membrane layer stacked in layers, the first membrane layer comprising a first fiber skeleton, the first fiber skeleton comprising a mixture, the mixture comprising sodium silicate and a first polymer, the second membrane layer comprising a second fiber skeleton, the second fiber skeleton comprising second polymer fibers, the second polymer fibers are partially wrapped with a phase change flame retardant material to form a necklace structure, wherein the phase change flame retardant material is (NH4)2·HPO4, the first polymer is polyethylene, the second polymer is polypropylene, the mass proportion of sodium silicate in the first membrane layer is 50.0%, and the mass proportion of the phase change flame retardant material in the second membrane layer is 20.0%.
[0174] This embodiment also provides a method for preparing the above-mentioned double-layer composite diaphragm, comprising the following steps:
[0175] 1. Preparation of (NH4)2·HPO4@PP composite membrane
[0176] 4 g of polypropylene and 36 ml of deionized water were placed in a tightly sealed glass bottle, which was placed in a 90°C oven for about 3 hours. When the polypropylene became transparent, it was taken out and magnetically stirred to completely dissolve it for spinning. The mass fraction of polypropylene was controlled to be 10%.
[0177] Take 6g (NH4)2·HPO4 powder and add it to a ball mill beaker. Mill it at 300rpm for 2h to make the particle size of (NH4)2·HPO4 0.7μm. Then, the (NH4)2·HPO4 after ball milling is evenly dispersed in anhydrous ethanol by ultrasonic treatment. Then, slowly add the (NH4)2·HPO4 suspension to the above polypropylene solution, stir and mix to form a uniform suspension, and then perform ultrasonic defoaming treatment before spinning.
[0178] Next, the mixed solution was loaded into a disposable syringe, mounted on an electrospinning push rod, the positive voltage was adjusted to 13 kV, the feed rate was set to 0.25 ml / min, and the solution was converted into a composite fiber membrane, i.e., a (NH4)2·HPO4@PP composite membrane, by electrospinning.
[0179] 2. Preparation of NaSiO3@PE composite membrane
[0180] Take 4g of polyethylene and 36ml of deionized water and put them into a tightly sealed glass bottle, put it into a 90℃ oven for about 3h, take it out when the polyethylene becomes transparent, and stir it magnetically to make it completely dissolved for spinning. The mass fraction of polyethylene is controlled to be 10%.
[0181] Take 2g NaSiO3 and disperse it evenly in 5ml deionized water. Then slowly add the NaSiO3 suspension to the above polyethylene solution, stir and mix to form a uniform milky white viscous solution, and ultrasonic defoaming treatment for spinning. Next, the above mixed solution is loaded into a disposable syringe, installed on the electrospinning push rod, the positive voltage is adjusted to 15kV, the feed rate is set to 0.1ml / min, and the solution is converted into a composite fiber diaphragm by electrospinning, that is, a NaSiO3@PE composite diaphragm.
[0182] 3. Preparation of double-layer composite membrane
[0183] Place the (NH4)2·HPO4@PP composite membrane (thickness B) and the NaSiO3@PE composite membrane (thickness A) in upper and lower layers with a thickness ratio of A / B of 1.5:1, then A / (A+B)=1.5:2.5. Put the fiber separator into an oven and heat treat it at 150°C for 2 hours under a pressure of 30 kPa to allow the fibers to fuse and increase the mechanical strength of the fiber membrane. The prepared membrane is a double-layer composite membrane.
[0184] Comparative Example 1
[0185] This comparative example provides a PVA diaphragm, which is different from Example 1 in that the diaphragm does not contain sodium silicate and phase change flame retardant material, and the thickness of the diaphragm is equal to A+B in Example 1.
[0186] The preparation method comprises the following steps:
[0187] Polyvinyl alcohol and deionized water were placed in a tightly sealed glass bottle, which was placed in a 90° C. oven for about 3 hours. When the polyvinyl alcohol became transparent, it was taken out and magnetically stirred to completely dissolve it for spinning. The mass fraction of polyvinyl alcohol was controlled to be 10%.
[0188] The mixed solution was loaded into a disposable syringe, mounted on an electrospinning push rod, the positive voltage was adjusted to 15 kV, the feed rate was set to 0.1 ml / min, and the solution was converted into a composite fiber membrane by electrospinning.
[0189] Comparative Example 2
[0190] This comparative example provides a NaSiO3@PVA composite diaphragm, which is different from Example 1 in that the diaphragm does not contain a Fe3P@PVA composite diaphragm.
[0191] The preparation method comprises the following steps:
[0192] 4 g of polyvinyl alcohol and 36 ml of deionized water were placed in a tightly sealed glass bottle, which was placed in a 90°C oven for about 3 hours. When the polyvinyl alcohol became transparent, it was taken out and magnetically stirred to completely dissolve it for spinning. The mass fraction of polyvinyl alcohol was controlled to be 10%.
[0193] Take 2g NaSiO3 and disperse it evenly in 5ml deionized water. Then slowly add the NaSiO3 suspension to the above polyvinyl alcohol solution, stir and mix to form a uniform milky white viscous solution, and ultrasonic defoaming treatment for spinning. Next, the above mixed solution is loaded into a disposable syringe, installed on the electrospinning push rod, the positive voltage is adjusted to 15kV, the feed rate is set to 0.1ml / min, and the solution is converted into a composite fiber diaphragm by electrospinning.
[0194] Comparative Example 3
[0195] This comparative example provides a double-layer composite diaphragm, which differs from Example 1 in that the NaSiO3@PVA composite diaphragm is replaced by a PVA diaphragm.
[0196] The preparation method comprises the following steps:
[0197] 1. Preparation of Fe3P@PVA composite membrane
[0198] 4 g of polyvinyl alcohol and 36 ml of deionized water were placed in a tightly sealed glass bottle, which was placed in a 90° C. oven for about 3 hours. When the polyvinyl alcohol became transparent, it was taken out and magnetically stirred to completely dissolve it for spinning. The mass fraction of polyvinyl alcohol was controlled to be 10%.
[0199] 2 g of Fe3P powder was added to a ball mill beaker and ball milled at 400 rpm for 3 h to make the Fe3P particle size 0.5 μm. The ball milled Fe3P was evenly dispersed in anhydrous ethanol by ultrasonic treatment. Then the Fe3P suspension was slowly added dropwise to the above polyvinyl alcohol solution, stirred and mixed to form a uniform suspension, and ultrasonic defoaming treatment was performed before spinning.
[0200] Next, the mixed solution was loaded into a disposable syringe, mounted on an electrospinning push rod, the positive voltage was adjusted to 15 kV, the feed rate was set to 0.1 ml / min, and the solution was converted into a composite fiber membrane, namely the Fe3P@PVA composite membrane, by electrospinning.
[0201] 2. Preparation of PVA membrane
[0202] 4 g of polyvinyl alcohol and 36 ml of deionized water were placed in a tightly sealed glass bottle, which was placed in a 90° C. oven for about 3 hours. When the polyvinyl alcohol became transparent, it was taken out and magnetically stirred to completely dissolve it for spinning. The mass fraction of polyvinyl alcohol was controlled to be 10%.
[0203] The mixed solution was loaded into a disposable syringe, mounted on an electrospinning push rod, the positive voltage was adjusted to 15 kV, the feed rate was set to 0.1 ml / min, and the solution was converted into a composite fiber membrane by electrospinning.
[0204] 3. Preparation of double-layer composite membrane
[0205] Place the upper and lower layers of Fe3P@PVA composite membrane PVA composite membrane with a thickness ratio of 1:1, put the fiber separator into an oven, and heat treat it at 200°C for 30 minutes under a pressure of 20 kPa to allow the fibers to fuse to increase the mechanical strength of the fiber membrane. The prepared membrane is a double-layer composite membrane.
[0206] Comparative Example 4
[0207] This comparative example provides a double-layer composite diaphragm, which differs from Example 1 in that the Fe3P@PVA composite diaphragm is replaced by a PVA diaphragm.
[0208] The preparation method comprises the following steps:
[0209] 1. Preparation of PVA composite membrane
[0210] 4 g of polyvinyl alcohol and 36 ml of deionized water were placed in a tightly sealed glass bottle, which was placed in a 90° C. oven for about 3 hours. When the polyvinyl alcohol became transparent, it was taken out and magnetically stirred to completely dissolve it for spinning. The mass fraction of polyvinyl alcohol was controlled to be 10%.
[0211] The mixed solution was loaded into a disposable syringe, mounted on an electrospinning push rod, the positive voltage was adjusted to 15 kV, the feed rate was set to 0.1 ml / min, and the solution was converted into a composite fiber membrane by electrospinning.
[0212] 2. Preparation of NaSiO3@PVA composite membrane
[0213] 4 g of polyvinyl alcohol and 36 ml of deionized water were placed in a tightly sealed glass bottle, which was placed in a 90°C oven for about 3 hours. When the polyvinyl alcohol became transparent, it was taken out and magnetically stirred to completely dissolve it for spinning. The mass fraction of polyvinyl alcohol was controlled to be 10%.
[0214] Take 2g NaSiO3 and disperse it evenly in 5ml deionized water. Then slowly add the NaSiO3 suspension to the above polyvinyl alcohol solution, stir and mix to form a uniform milky white viscous solution, and ultrasonic defoaming treatment for spinning. Next, the above mixed solution is loaded into a disposable syringe, installed on the electrospinning push rod, the positive voltage is adjusted to 15kV, the feed rate is set to 0.1ml / min, and the solution is converted into a composite fiber diaphragm by electrospinning, that is, a NaSiO3@PVA composite diaphragm.
[0215] 3. Preparation of double-layer composite membrane
[0216] Place the PVA composite membrane and the NaSiO3@PVA composite membrane as upper and lower layers with a thickness ratio of 1:1. Put the fiber separator into an oven and heat treat it at 200°C for 30 minutes under a pressure of 20 kPa to allow the fibers to fuse and increase the mechanical strength of the fiber membrane. The prepared membrane is a double-layer composite membrane.
[0217] Comparative Example 5
[0218] This comparative example provides a Fe3P@PVA composite diaphragm, which is different from Example 1 in that the diaphragm does not contain a NaSiO3@PVA composite diaphragm.
[0219] The preparation method comprises the following steps:
[0220] 4 g of polyvinyl alcohol and 36 ml of deionized water were placed in a tightly sealed glass bottle, which was placed in a 90°C oven for about 3 hours. When the polyvinyl alcohol became transparent, it was taken out and magnetically stirred to completely dissolve it for spinning. The mass fraction of polyvinyl alcohol was controlled to be 10%.
[0221] 2 g of Fe3P powder was added to a ball mill beaker and ball milled at 400 rpm for 3 h to make the Fe3P particle size 0.5 μm. The ball milled Fe3P was evenly dispersed in anhydrous ethanol by ultrasonic treatment. Then the Fe3P suspension was slowly added dropwise to the above polyvinyl alcohol solution, stirred and mixed to form a uniform suspension, and ultrasonic defoaming treatment was performed before spinning.
[0222] Next, the mixed solution was loaded into a disposable syringe, mounted on an electrospinning push rod, the positive voltage was adjusted to 15 kV, the feed rate was set to 0.1 ml / min, and the solution was converted into a composite fiber membrane, namely the Fe3P@PVA composite membrane, by electrospinning.
[0223] Battery preparation:
[0224] Preparation of negative electrode sheet: Lithium foil is used as the negative electrode active material and bonded to copper foil. The size of the negative electrode sheet is (100 mm × 55 mm).
[0225] Preparation of positive electrode: using ternary material NCM811 (chemical formula LiNi 0.8 Co 0.1 Mn 0.1 O2) is used as the positive electrode active material, which is mixed with the conductive agent SP and the binder PVDF in a mass ratio of 97:2:1, coated on aluminum foil, and made into a positive electrode sheet after drying, pressing and other processes. The size of the positive electrode sheet is 96mm×51mm.
[0226] The separators prepared in the respective Examples and Comparative Examples were used as separators.
[0227] The electrolyte is obtained by dissolving 1 mol / L LiPF6 in a solvent, and the solvent is a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1.
[0228] For the full cell, the capacity ratio of the positive electrode to the negative electrode is 1.2, and the loading of the negative electrode is 9.8 mg cm -2 .
[0229] The assembly process adopts the soft pack lamination method. Specifically, the lamination process is: stack the positive electrode sheet, the diaphragm, and the negative electrode sheet in order to obtain a battery cell. Assembly: The stacked battery cell is hot-pressed and placed in an aluminum-plastic film for top and side sealing. Injection: The electrolyte is injected into the battery, wherein the solvent of the electrolyte is a mixed solvent of EC, EMC and DEC, and the volume ratio satisfies Vol (EC: EMC: DEC) = 2: 1: 2, and the solute is 1 mol / L lithium hexafluorophosphate. Packaging: The battery after injection is sealed, and the injection coefficient is 3g / Ah. Formation: The packaged battery is subjected to formation treatment.
[0230] Test methods and test conditions:
[0231] (1) Porosity test of diaphragm: mercury intrusion method. The results are shown in Table 1.
[0232] (2) The contact angle test of the diaphragm was carried out using a contact angle measuring instrument. The electrolyte (the composition of the electrolyte used in the above-mentioned battery assembly) was dripped onto the surface of the diaphragm. Note that when the diaphragm contains the Fe3P@PVA composite diaphragm, the contact angle of this side surface is measured. The results are shown in Table 2. The size of the contact angle can reflect the electrolyte affinity of the diaphragm.
[0233] (3) Test of high temperature shrinkage of diaphragm: The diaphragm is placed at a certain temperature (120°C, 160°C or 200°C) for 1 hour, and the area shrinkage rate of the diaphragm is calculated using the formula: Area shrinkage rate = (area before shrinkage - area after shrinkage) / area before shrinkage. The results are shown in Table 3.
[0234] (4) The electrochemical performance of the battery was tested. The charge and discharge cut-off voltage was set to 2.8-4.2 V, the charge and discharge current was set to 1 A / g, and the test was terminated after 2000 cycles. The first efficiency and 2000-cycle capacity retention rate were recorded. The results are shown in Table 4.
[0235] Table 1
[0236]
[0237] As shown in Table 1, the double-layer composite diaphragm of the present invention has a high porosity, which can ensure that Li + Fast passage, promote Li + It is uniformly deposited on the anode side to form a stable SEI film, which is beneficial to improving the electrochemical performance of the battery; at the same time, the high porosity is beneficial to improving the electrolyte retention rate of the diaphragm. The porosity of the diaphragms of Comparative Examples 1-5 is reduced to varying degrees compared with Example 1, which shows that designing the diaphragm into a double-layer structure and wrapping Fe3P particles and dispersed sodium silicate in the two layers is beneficial to improving the porosity.
[0238] Table 2
[0239]
[0240] It can be seen from Table 2 that the double-layer composite diaphragm of the present invention can fully reduce the contact angle of the diaphragm and accelerate the wetting, indicating that it has good electrolyte wettability. At the same time, through the comparison of Example 1 and Comparative Examples 1-5, it can be seen that the introduction of Fe3P is conducive to improving the electrolyte wettability of the diaphragm.
[0241] Table 3
[0242]
[0243] It can be seen from Table 3 that the double-layer composite diaphragm of the present invention has good heat shrinkage resistance. Through the comparison of Example 1 and Comparative Examples 1-5, it can be seen that the introduction of Fe3P and sodium silicate into the diaphragm is beneficial to improving the heat resistance of the diaphragm, and sodium silicate has a better improvement on heat resistance.
[0244] Table 4
[0245]
[0246] As shown in Table 4, the battery assembled with the double-layer composite separator of the present invention exhibits good electrochemical performance, high initial efficiency and good cycle performance. However, the electrochemical performance of Comparative Examples 1-5 is reduced to varying degrees compared with the examples.
[0247] At the same time, by comparing Example 1 with Examples 7-8, it can be seen that there is a preferred range between the thickness of the first film layer and the second film layer. When the thickness A of the first film layer and the thickness B of the second film layer satisfy the relationship: 1 / 3≤A / (A+B)≤2 / 3, the wettability of the diaphragm is good, and the ionic conductivity and the uniform deposition of lithium ions are good. Therefore, the rate performance and cycle performance of the battery are improved.
[0248] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A double-layer composite diaphragm, characterized in that: The double-layer composite diaphragm includes a first film layer and a second film layer stacked in layers, the first film layer includes a first fiber skeleton, the first fiber skeleton includes a mixture, the mixture includes sodium silicate and a first polymer, the second film layer includes a second fiber skeleton, the second fiber skeleton includes a second polymer fiber, and the second polymer fiber is partially wrapped with a phase change flame retardant material to form a necklace structure; The thickness of the first film layer is A, the thickness of the second film layer is B, 1 / 3≤A / (A+B)≤2 / 3; The mass proportion of the sodium silicate in the first film layer is 33.3%-50.0%; The mass proportion of the phase change flame retardant material in the second film layer is 20.0%-50.0%.
2. The double-layer composite diaphragm according to claim 1, characterized in that: The phase change flame retardant material comprises at least one of Fe3P, (NH4)2·HPO4, (NH4)·H2PO4, aluminum hydroxide, magnesium hydroxide, red phosphorus, ammonium polyphosphate, zinc borate and antimony oxide; and / or, The first polymer includes at least one of polyvinyl alcohol, polyvinylidene fluoride, polypropylene, polyethylene, polyethylene terephthalate, polymethyl methacrylate and polyethylene oxide; and / or, The second polymer fiber includes at least one of polyvinyl alcohol, polyvinylidene fluoride, polypropylene, polyethylene, polyethylene terephthalate, polymethyl methacrylate, and polyethylene oxide.
3. The double-layer composite diaphragm according to claim 1, characterized in that: The porosity of the double-layer composite diaphragm is 37%-46%.
4. A method for preparing a double-layer composite diaphragm according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) Providing electrospinning solution: adding sodium silicate to the first polymer glue to obtain a first solution; Adding a phase change flame retardant material to the second polymer glue to obtain a second solution; (2) Electrospinning: Electrospinning is performed using the first solution and the second solution respectively to obtain a first spinning membrane and a second spinning membrane; (3) Hot pressing treatment: The first spinning membrane and the second spinning membrane are stacked together and hot pressed to obtain the double-layer composite membrane, which includes a first membrane layer and a second membrane layer stacked together, wherein the first spinning membrane forms the first membrane layer and the second spinning membrane forms the second membrane layer.
5. The preparation method according to claim 4, characterized in that: Step (1) The viscosity of the first polymer glue is μ1,50cP≤μ1≤20000cP; and / or, After the sodium silicate is added, heating and stirring are performed to form a first solution in a gel state; and / or, Step (1) The viscosity of the first solution is μ2, 50 cP ≤ μ2 ≤ 30000 cP; and / or, Step (1) The viscosity of the second polymer glue is μ3, 50 cP≤μ3≤20000 cP; and / or, After the phase change flame retardant material is added, heating and stirring are performed to form a second solution in a gel state; and / or, The viscosity of the second solution in step (1) is μ4, 50 cP≤μ4≤30000 cP.
6. The preparation method according to claim 4, characterized in that: In step (2), the volume V1 of the first solution and the volume V2 of the second solution satisfy: 1 / 3≤V2 / (V2+V1)≤2 / 3.
7. The preparation method according to claim 4, characterized in that: The temperature of the hot pressing in step (3) is 80°C-220°C; and / or, The hot pressing pressure in step (3) is 10 kPa-30 kPa; and / or, The hot pressing time in step (3) is 0.5h-10h.
8. A battery comprising a positive electrode, a negative electrode, a separator and an electrolyte, characterized in that: The diaphragm is a double-layer composite diaphragm according to any one of claims 1 to 3 or a double-layer composite diaphragm prepared by the method according to any one of claims 4 to 7, wherein the first film layer is arranged close to the negative electrode, and the second film layer is arranged close to the positive electrode.
Citation Information
Patent Citations
Hydroxyapatite super-long nanowire-based high-temperature-resistant battery diaphragm and application thereof
CN107565081A
Separator for lithium-ion secondary battery
JP2013127955A